Ice-free valleys in the Neptune Range of the Pensacola Mountains, Antarctica: glacial geomorphology, geochronology and potential as palaeoenvironmental archives. Issue 4 (August 2021) - Small, David; Bentley, Michael J.; Evans, David J.A.; Hein, Andrew S.; Freeman, Stewart P.H.T.
Abstract: We describe the glacial geomorphology and initial geochronology of two ice-free valley systems within the Neptune Range of the Pensacola Mountains, Antarctica. These valleys are characterized by landforms associated with formerly more expanded ice sheet(s) that were at least 200 m thicker than at present. The most conspicuous features are areas of supraglacial debris, discrete debris accumulations separated from modern-day ice and curvilinear ridges and mounds. The landsystem bears similarities to debris-rich cold-based glacial landsystems described elsewhere in Antarctica and the Arctic where buried ice is prevalent. Geochronological data demonstrate multiple phases of ice expansion. The oldest, occurring > 3 Ma, overtopped much of the landscape. Subsequent, less expansive advances into the valleys occurred > 2 Ma and > 1 Ma. An expansion of some local glaciers occurred < 250 ka. This sequence of glacial stages is similar to that described from the northernmost massif of the Pensacola Mountains (Dufek Massif), suggesting that it represents a regional signal of ice-sheet evolution over the Plio-Pleistocene. The geomorphological record and its evolution over millions of years makes the Neptune Range valleys an area worthy of future research and we highlight potential avenues for this.